Contribution to syntheses of some azomethines of 5-amino-1-methyl-2-phenylindole series - Thanh et al, Nguyen Dinh (Vietnam Journal of Chemistry, 2014)
Ten azomethines of 5-amino-1-methy-2-phenyllindole series have been synthesized by reaction between these amines and substituted benzaldehyde. The structures of obtained compounds have been confirmed by using spectroscopic methods, such as IR, mass, 1H-NMR, 13C-NMR spectra with two-dimensional experiments (HSQC and HMBC).